The degree of availability of the learning organization dimensions in light of the Senge model in general education schools - Al-Maawy, Reem Mohammed; Alghamdi, Hanan Hassan (Journal of Educational and Psychological Sciences, 2024)
The research aimed to identify the degree of availability of the dimensions of Senge in the following areas (personal empowerment, mental models, shared vision, systems thinking, teamwork as a team) in general education schools, and to reveal whether there are statistically significant differences between members of the research community. About the degree of availability of the dimensions of the Senge model according to the research variables (gender, educational qualification, educational level, years of experience). To achieve the objectives of the research, the researcher used the descriptive survey approach, and the research community was represented in all the leaders of the intermediate and secondary levels for boys and girls in the Middle Education Office in Bisha governorate, and their number was (105) leaders, while the study sample consisted of (81) leaders and female leaders. The study reached several results, the most prominent of which are: 1-The total availability level of the learning organization dimensions in light of the Singh model in general education schools obtained an arithmetic mean value (4.21) and a very high degree of availability. The mental models dimension came in first place with an arithmetic mean of (4.24) and a very high degree of availability, followed by the dimension of group learning as a team, which obtained an arithmetic mean of (4.22) and a very high degree of availability, followed by both the common vision dimension and the systemic thinking dimension, where each of them happened. He obtained an arithmetic average of (4.2) and a very high degree of availability, while after personal ability he obtained an arithmetic mean of (4.16) and a high degree of availability. 2-The absence of statistically significant differences between the study sample responses with regard to the level of availability of the learning organization dimensions in light of the Singh model in public education schools due to the gender variable, academic qualification, academic stage, or years of experience.
Keywords: Learning Organization; SING Model; General Education Schools